2019
DOI: 10.1109/ted.2019.2909152
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Packaged GaN Power Transistors Parasitics Using S-Parameters

Abstract: In order to better predict the high frequency switching operation of transistors in power converters, the access elements of these devices like resistances and inductances must be accurately evaluated. This paper reports on the characterization of a gallium nitride (GaN) packaged power transistor using S-parameters in order to extract the parasitics stemming from ohmic contacts and packaging. As the transistor is encapsulated, a calibration technique is set using specific test fixtures designed on FR4 printed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In order to increase attention for high‐temperature and high‐power applications at high frequencies, the kink effects are investigated in the output reflection coefficient (S 22 ) and the short‐circuit current gain (h 21 ) to be shown how these phenomena affect the applications of electronic devices . At first, the S parameters are analyzed completely that S 11 and S 22 on Smith charts and S 21 and S 12 on polar plots are reported . The S parameters are investigated from 1 KHz to 100 GHz at V DS = 20 V and V GS = −1.5 V and as it is shown that the kink effect has the impressive influence on all the S parameters in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase attention for high‐temperature and high‐power applications at high frequencies, the kink effects are investigated in the output reflection coefficient (S 22 ) and the short‐circuit current gain (h 21 ) to be shown how these phenomena affect the applications of electronic devices . At first, the S parameters are analyzed completely that S 11 and S 22 on Smith charts and S 21 and S 12 on polar plots are reported . The S parameters are investigated from 1 KHz to 100 GHz at V DS = 20 V and V GS = −1.5 V and as it is shown that the kink effect has the impressive influence on all the S parameters in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…S-parameter characterization has demonstrated a good accuracy to extract low inductance values in the nanohenry range up to the gigahertz [20,21]. In order to perform accurate S-parameter measurements on a PCB commutation loop, test fixtures associated with a specific calibration method were developed.…”
Section: Calibration Proceduresmentioning
confidence: 99%
“…The proposed model is based on EM/circuit co-simulations and an experimental extraction of the parasitic inductance including GaN device packaging effects using S-parameter measurements over the frequency range 1-500 MHz. The S-parameters method is an accurate microwave measurement technique showing accuracy to extract parasitics in power devices [20][21][22][23]. In this study, it is proposed to extend existing techniques to the characterization of parasitic elements in a commutation cell.…”
Section: Introductionmentioning
confidence: 99%
“…SPICE-based simulation tools, PSIM and ANSYS Simplorer are among standard circuit simulation tools. The parameters for these models are extracted from measurements and/or the device datasheet [57], [58].…”
Section: B Switching Devicesmentioning
confidence: 99%